Peningkatan Akuakultur Di Wilayah Jawa Timur Melalui Strategi Inovasi Dengan Pendekatan Matriks TOWS - Rianawati, Andri; Darmasetiawan, Noviaty Kresna; Hadi, Faizal Susilo; D'Surya, Lucan Feliciano; Oktavianus, Joshua (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study investigates innovation strategies for aquaculture in East Java using SWOT analysis and TOWS matrix. Although East Java is one of the three largest contributors in aquaculture in Indonesia, maintaining its sustainability is highly dependent on the right strategy based on environmental conditions. This research used a qualitative method with data collection techniques involving in-depth interviews with 7 informants from various backgrounds. The research findings revealed East Java's strengths in terms of community cohesiveness and adaptability to limitations, but a one-time business cycle due to limited capital and low levels of domestic consumption. Some opportunities still arise, such as East Java's high fisheries export demand and capability and the support of a government program called 'Gemarikan'. On the other hand, its vulnerability to weather, water, budget fluctuations, and poor business practices may pose a threat. As a result, the TOWS Matrix identified several innovation strategies for aquaculture in East Java, namely improving aquaculture literacy and knowledge transfer, community-based improvement, and bottom-up collaborative coordination.